Chapter Modelling Neurodegenerative Diseases Using Human Pluripotent Stem Cells - Hall, Vanessa J. (InTechOpen, 2016)
Biomarkers offer a way to speed up medical research by shedding light on the physiopathological mechanisms of disease. Furthermore, biomarkers are considered invaluable tools for monitoring disease progression, prognosis, and response to drugs, especially in clinical trials, where they can be used to assess the efficacy, efficiency, and side effects of novel drugs.